Clinical learning experiences and professional development: implementation of a district level undergraduate midwifery program in Indonesia - Eva Rusdianah; Mubasysyir Hasanbasri; Mohammad Hakimi (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
PurposeThe aim is to examine the suitability of the educational process in place with the expected professional development.MethodWe conducted in-depth interviews with (a) 16 third-year student who recently completed 2-month clinical rotation in the hospital and (b) four teachers.ResultsEvidence from this study indicate weak learning environment. Clinical instructor only has a limited time to meet with students, so that students rarely get the guidance and direct supervision. Students more often obtain “lessons” of the young staff, which many of them indifferent in providing guidance. Students feel insecure and fear in communicating with senior staff from both the nursing and medical professions. Academic lecturers provide minimum learning support. Their supervision does not allow students to reflect on their experiences.ConclusionProfessional development as reflected in clinical rotations in hospitals is still very limited. The government must monitor more strictly, especially for the medical school located in the district, where professional educators are very limited.